2006
DOI: 10.1149/1.2214563
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Mitigation of PFSA Polymer Degradation in PEM Fuel Cells

Abstract: This paper describes approaches to reduce susceptibility of perfluorosulfonic acid membranes such as Nafion® to degradation through chemical attack by oxygen-based radicals and physical degradation as a result of mechanical stress. These approaches include the incorporation of a continuous reinforcing layer and modification of the polymer to stabilize it against attack by peroxide radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…Commercial Nafion 212 membrane and the modified Nafion 212 membrane with CeO 2 layers with different coating densities were immersed in a Fenton solution (20 wt.% H 2 O 2 , 30 ppm Fe 2+ ) at 80 C for 72 hours. Hydroxyl radicals (OH•) were generated via this process as follows [51][52][53] :…”
Section: Characterizations Of Nafion Composite Membrane With Ceo 2 La...mentioning
confidence: 99%
“…Commercial Nafion 212 membrane and the modified Nafion 212 membrane with CeO 2 layers with different coating densities were immersed in a Fenton solution (20 wt.% H 2 O 2 , 30 ppm Fe 2+ ) at 80 C for 72 hours. Hydroxyl radicals (OH•) were generated via this process as follows [51][52][53] :…”
Section: Characterizations Of Nafion Composite Membrane With Ceo 2 La...mentioning
confidence: 99%
“…50 kcal/mol), consistent with prior studies 30,[46][47] (Supporting Information Table S10). Nevertheless, to explain experimental observations of trace [35][36] HF formed in ex situ experiments on Nafion 9,35 , we must either expect spontaneous generation of radicals capable of directly abstracting fluorine (e.g., H radical) or some alternative pathway for degradation of terminal carbon radicals formed (e.g., y1c) from C-S bond cleavage (Figure 6). One possibility that is consistent with experiments 11,19 would involve the continued degradation by an OH radical of a terminal carbon radical with moderate barriers similar to the equivalent steps considered on defect-containing Nafion (e3 to e7 in Figure 5 and Supporting Information Figure S4).…”
Section: C Degradation Mechanisms At Sulfonic Acid Functional Groupsmentioning
confidence: 99%
“…Fluoride release measurements conducted after ex situ Fenton's degradation tests indicate the release of more HF from defect-containing membranes than from defect-free ones 32,35 , indeed suggesting that such defects are more prone to radical attack. Even though defects are the most vulnerable sites for attack by OH radicals during ex situ degradation, Nafion still degrades in the absence of defects 9,32,[35][36] , as evidenced through some release of HF 9,35 .…”
Section: Introductionmentioning
confidence: 99%
“…;000 Â 60 Â 60 (9) This ensures that the covariance would propagate in such a way that after 40,000 h, two standard deviations of the EMSA would encompass a 10% decline from the initial value with no updates from the measurements.…”
Section: Extended Kalman Filtering Algorithm For Mea Statementioning
confidence: 99%
“…[6] and [7]. Studies have shown that the degradation rate is affected by the frequency and duration of open circuit voltage (OCV) instances [8][9][10][11][12], low humidity operation [13][14][15][16], high humidity operation [17,18], and by the operating temperature [7]. In general, degradation tends to become worse with temperatures above 75 C, the use of gases that are not fully humidified, and with load cycling, particularly if the OCV potential is included [7].…”
Section: Introductionmentioning
confidence: 99%